Analisis Kerangka Kerja Scrum pada Sistem Informasi SIGAP sebagai Model Transformasi Digital Kepolisian - Hartomo, Kristoko; Arthur, Christian; Waliyuddin Rabbani, Imam (Jurnal Algoritma, 2025)
The advancement of information technology has driven law enforcement institutions to pursue digital transformation in order to enhance the effectiveness and accountability of public services. One of the initiatives undertaken by the Magelang City Police is the development of the Security Guard Information System (SIGAP), designed to support activity recording, field monitoring, personnel management, and security reporting. Common challenges in similar system developments include excessive backlog, release delays, and limited user involvement. This study aims to analyze the application of the Scrum framework in the development of SIGAP, evaluate its impact on team performance and stakeholder engagement, and provide practical contributions to the adoption of Agile methods in the public sector. This research employed a case study approach using Scrum, conducted through four sprints of two weeks each. Data were collected through observation, interviews, questionnaires, and application log analysis. Evaluation indicators included backlog completion rate, average cycle time, user satisfaction, and stakeholder participation. The findings indicate that backlog completion increased from 24% in the first sprint to 100% in the fourth sprint, accompanied by a 65% reduction in cycle time. User satisfaction improved from a moderate level to a very good level, while stakeholder participation increased from 60% to 93%. These results demonstrate that the Scrum framework is effective in enhancing the development of police information systems and can serve as a replicable model for adaptive, transparent, and accountable digital transformation in other public institutions.